Characterizing dysphagia after spinal surgery. (3rd September 2021) - Miles, Anna; Jamieson, Gabi; Shasha, Lara; Davis, Kelly
Abstract : Context/Objective: Dysphagia after spinal surgery is well recognised. Characteristics of post-operative dysphagia are not well defined. This study explored severity, longevity, and physiological characteristics of dysphagia. Design: Prospective, observational study. Setting: Tertiary urban hospital. Participants: Two-hundred fifty patients consecutively receiving spinal surgery. Interventions: Demographic and clinical information were collected. Flexible endoscopic evaluation of swallowing (FEES) and videofluoroscopic study of swallowing (VFSS) recordings were analyzed. Outcomes Measures: FEES recordings were analyzed using three validated symptom scales. VFSS recordings were analyzed using 10 objective digital measures of timing, displacement and symptoms. Results: Of 250 patients, 75 were referred for swallowing assessment. Sixty-two received FEES and 11 VFSS. Patients with anterior approach surgery for cervical level injuries represented 85% of referrals ( n = 64). Secretion accumulation, aspiration and residue scores decreased significantly within 2 months for most patients. For those with persisting dysphagia, objective VFSS measures demonstrated significant impairments in pharyngeal constriction, hyoid displacement and pharyngoesophageal segment opening with corresponding residue and aspiration scores. By 6 months, all patients had returned to a regular diet except three patients following anterior cervical discectomy and fusion (ACDF) who remained nil by mouth with severe physiological impairments. Conclusions: A quarter of patients following spinal surgery present with dysphagia. For most, symptoms decrease significantly by 2 months and patients return to normal diets. Early screening of dysphagia is critical to avoid secondary complications and prolonged hospitalizations. For some, significant pharyngeal impairments persist and high-quality case series exploring efficacy of rehabilitation programmes are needed.